The traditional Chinese medicine formula Zhihan Anshen Tang (ZHAST) against obstructive sleep apnea hypopnea syndrome: network pharmacology and molecular docking approach - Cai-Li Li; Yu-Xiang Zhang; Xing-Jie Zheng; Shuo Li; Jing Feng (Frontiers in Chemistry)
IntroductionThe current treaments for Obstructive Sleep Apnea Hypopnea (OSAHS) are Continuous Positive Airway Pressure (CPAP) and lifestyle modifications, which is not suitable for all patients. Traditional Chinese medicine (TCM) has increasingly demonstrated its efficacy and benefits in treating OSAHS. Zhihan Anshen Tang (ZHAST), has been demonstrated its efficacy and clinical metrics for treating OSAHS patients. However, its key ingredients and mechanisms of action are still unknown.MethodsUsing network pharmacology, we investigated the potential mechanisms of ZHAST through which OSAHS.ResultsIn addition, the key targets, including TNF, IL6, GAPDH, STAT3, HIF1A, and JUN, are revealed by the topological analysis. According to the findings of the GO enrichment analysis, genes were enriched in inflammatory responses, hypoxia responses, positive regulation of angiogenesis, protein phosphorylation, and regulation of cell proliferation. KEGG pathway enrichment analysis suggests that the signaling pathway of ZHAST in OSAHS are MAPK and AGE-RAGE signaling pathway, especially in diabetic complications. In addition, it is demonstrated that the enoxolone in ZHASTs have high affinity with the relevant targets by molecular docking and molecular dynamics simulations.DisscussionTo my knowledge, this is the first network pharmacological molecular docking study about a Chinese medicine effective against OSA. This investigation integrates molecular docking and network pharmacology to identify the effective compounds, related targets, and potential mechanism of ZHASTs in the treatment of OSAHS, providing the prospect of traditional Chinese medicines with modern medical research.